Self-Compassion Contribution to Body Image on Students at SMK Negeri 1 Karanganyar, Ngawi - Yori Ninda Pusvitasari; Eni Rindi Antika; Mohd Hardyman Barawi; Abang Izhar Abang Ahmad; Zaimuariffudin Shukri Nordin (State Islamic University (UIN) Salatiga, 2024)
This study aims to measure the contribution of self-compassion to the body image of students of SMKN 1 Karanganyar. The approach used in this research is a quantitative approach with an ex-post-facto design. The sample in this study amounted to 279 students from a total population of 926 students who were taken using a proportionate stratified random sampling technique. The instrument used is a self-compassion scale developed by researchers based on Neff's (2015) theory, which totals 29 items, and a body image scale developed based on Cash and Pruzinsky's (2002) theory, totaling 41 items. The validity test results for the self-compassion scale get a value range of 0.493-0.731, and the body image scale has a value range of 0.271-0.659. The reliability test results of the self-compassion scale obtained results of 0.918 and the body image scale of 0.947. Hypothesis testing using simple linear regression analysis with the results showed that self-compassion contributed 31.4% with the coefficient of determination (R2 = 0.314, ρ < 0.05). Based on these results, it can be seen that self-compassion significantly influences body image in SMK Negeri 1 Karanganyar students. Future researchers can research other variables that affect body image, such as gratitude, self-esteem, and social comparison.